Predictive factors for the admission of a newborn in an intensive care unit - Lages, Carla Danielle Ribeiro (2014)
Analytical documentary and retrospective study aiming at determining association between predictive factors for admission of a newborn in a public Intensive Care Unit and maternal features. The study sample had 376 neonates admitted in 2009. Results showed: mothers aged between 19 and 25 years (43.4%), primary education (52.4%), living with a partner (66.2%). Prenatal care was done by 84.8% of them, and 62% presented gestational pathologies. Out of all neonates, 55.1% were male, 85.4% preterm, 83% underweight, 57.2% presented respiratory problems. The bivariate analysis showed a significant association between birth weight and growth (p = 0.04) between maternal age and Apgar in the 1st minute (p = 0.04) and maternal age and Apgar score in the 5th minute (p = 0.01). Maternal age and number of prenatal appointments influence on the admission of the neonates to the Intensive Care Unit because they are related to birth weight and Apgar scores.